Genetic Diversity and Chemical Polymorphism of Some Thymus Species. Issue 6 (18th June 2013) - Rustaiee, Ali Reza; Yavari, Alireza; Nazeri, Vahideh; Shokrpour, Majid; Sefidkon, Fatemeh; Rasouli, Musa
Abstract To ascertain whether there are chemical and genetic relationships among some Thymus species and also to determine correlation between these two sets of data, the essential‐oil composition and genetic variability of six populations of Thymus including: T. daenensis Čelak. (two populations), T. fallaxFisch. & C.A.Mey., T. fedtschenkoiRonniger, T. migricusKlokov & Des.‐Shost., and T. vulgaris L. were analyzed by GC and GC/MS, and also by randomly amplified polymorphic DNA (RAPD). Thus, 27 individuals were analyzed using 16 RAPD primers, which generated 264 polymorphic scorable bands and volatiles isolated by distillation extraction were subjected to GC and GC/MS analyses. The yields of oils ranged from 2.1 to 3.8% (v/w), and 34 components were identified, amounting to a total percentage of 97.8–99.9%. RAPD Markers allowed a perfect distinction between the different species based on their distinctive genetic background. However, they did not show identical clustering with the volatile‐oil profiles.